Low-vision rehabilitation in Italy: Cross-sectional data from the Device and Aids Registry (D.A.Re). Issue 4 (July 2022) - Bartolomei, Federico; Biagini, Ilaria; Sato, Giovanni; Falchini, Elisabetta; Di Simone, Alessia; Mastrantuono, Chiara; Micarelli, Silvia; Virgili, Gianni
Objectives: We are reporting on the characteristics of low-vision adults attending large rehabilitation services which provide data to D.A.Re (Devices & Aids REgister) in Italy. D.A.Re aims to gather information about low-vision aids owned by Italian patients with visual impairment. Methods: We included consecutive patients attending low-vision rehabilitation centres providing data to D.A.Re from 2019 to July 2021. Demographic features, self-reported use of technology and aids, vision performance, and the Instrumental Activity of Daily Living (IADL) score were collected. Results: 720 patients were included in the D.A.Re. About half of the patients were affected by Age-related Macular Degeneration (389, 54.9%). Patients reported a long interval between onset of vision disability and access to low-vision rehabilitation, which was over two years in almost 30% of cases. Blindness registration status was almost complete when reported, but almost 40% were unable to report on this. IADL scores were higher for younger people and those with better visual acuity and critical print size (CPS), and lower for visual field restriction ( p  < 0.01 for all predictors). Of interest, better IADL scores were recorded for those with computer knowledge who used optical aids and software in univariate analyses and multivariate analyses, adjusting for level of visual disability and employment status ( p  < 0.01 for all predictors). Conclusions: We report on the profile of low-vision patients using rehabilitation services in Italy. Longitudinal data during and after vision rehabilitation were collected. Our results support the validity of the D.A.Re to monitor the use of low-vision devices in Italy.